Edukasi Swamedikasi Rasional melalui Gerakan Masyarakat Cerdas Menggunakan Obat (GeMa CerMat) pada Komunitas Keluarga Alumni Pondok Pesantren Inayatullah di Sleman - Dilalah, Idlohatud; Christiandari, Hanita; Hernawan, Jarot Yogi; Suprasetya, Edy; Laila, Wahyu Kumil; Nugraheni, Nadzifa (Jurnal Pengabdian Masyarakat Permata Indonesia, 2025)
Self-medication refers to an individual’s effort to treat their own health complaints based on symptoms they experience. This practice commonly involves purchasing over-the-counter drugs, using leftover prescribed medicines, or taking medications recommended by family members, friends, or the media without medical supervision. Such self-treatment carries the risk of irrational drug use; therefore, education is essential to enhance public literacy regarding the proper use of medicines. The Inayatullah Islamic Boarding School Alumni Family Community consists of former students and their families, most of whom are in the 25–35 age range and have recently started families. This community service program aims to improve participants’ knowledge and attitudes toward self-medication through a community-based educational approach. The activity was implemented through the Smart Community Movement for the Rational Use of Medicines (GeMa CerMat), conducted in the form of interactive lectures and discussions during a regular monthly gathering at one of the alumni’s residences in Dukuh Nandan, Sariharjo Village, Ngaglik District, Sleman Regency. Participants actively engaged in discussions about appropriate and rational self-medication practices. It is expected that this educational initiative will enhance the community’s understanding of responsible self-medication, enabling them to make wiser decisions in treating minor health problems and to prevent irrational drug use.